Pengaruh Dosis Vermikompos dan Pupuk ZA terhadap Pertumbuhan dan Produksi Kacang Panjang (Vigna sinensis L.) - Dwita Ulandari; Nanik Setyowati; Sigit Sudjatmiko; Widodo Widodo; Zainal Muktamar (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Ulandari D, Setyowati N, Sudjatmiko S, Widodo W, Muktamar Z. 2021. Effect of vermicompost and ammonium nitrate dosage on growth and yield of long beans (Vigna sinensis L.) In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 514- 523. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). The production of long beans (Vigna sinensis L.) can be increased through intensification or extensification, respectively. Intensification includes soil management activities, selection of superior varieties, pest and disease control, and fertilization. Fertilization is necessary for the improvement of long beans yield. The combination of organic and synthetic is necessary to maintain soil productivity. Such combination is vermicompost and ammonium nitrate fertilizer. The purpose of this study was to ascertain the effect of a combined dose of vermicompost and ammonium nitrate on long bean growth and yield. The study used Randomized Complete Block Design (RCBD) with 3 replications. The treatments were Vermicompost (V) 15 tons/ha, ZA 50 kg/ha, V 15 tons/ha + ZA 50 kg/ha, (V 15 tons/ha + ZA 100 kg/ha, V 15 tons/ha + ZA 150 kg/ha, V 15 tons/ha + ZA 200 kg/ha, and V 15 tons/ha + ZA 250 kg/ha. The results indicated that applying vermicompost alone or with ZA had no noticeable effect on plant growth and yield. There were no significant differences in plant height, pod length, pod diameter, number of seeds, number of pods, or pod weight between treatments. Long bean productivity is lower than its potential yield due to unfavorable environmental factors.